Industrial concessions, fires and air pollution in Equatorial Asia - Spracklen, D.V.; Reddington, C.L.; Gaveau, D.L.A. (IOP Publishing, 2015)
Forest and peatland fires in Indonesia emit large quantities of smoke leading to poor air quality across Equatorial Asia. Marlier et al (2015 Environ. Res. Lett. 10 085005) explore the contribution of fires occurring on oil palm, timber (wood pulp and paper) and natural forest logging concessions to smoke emissions and exposure of human populations to the resulting air pollution. They find that one third of the population exposure to smoke across Equatorial Asia is caused by fires in oil palm and timber concessions in Sumatra and Kalimantan. Logging concessions have substantially lower fire emissions, and contribute less to air quality degradation. This represents a compelling justification to prevent reclassification of logging concessions into oil palm or timber concessions after logging. This can be achieved by including logged forests in the Indonesian moratorium on new plantations in forested areas.